Penerapan Asas Itikad Baik Dalam Hukum Perikatan: Antara Kepastian Hukum Dan Keadilan Kontraktual - Lulu Syakirah Alatas; Nur Sa'adah (Consensus : Jurnal Ilmu Hukum, 2026)
The principle of good faith constitutes one of the fundamental principles in the law of obligations governing the implementation of agreements between parties. Within the Indonesian civil law system, this principle is regulated in the Civil Code, particularly Article 1338 paragraph (3), which stipulates that agreements must be executed in good faith. However, in practice, the application of this principle frequently gives rise to various issues because the concept of good faith is inherently abstract and allows for broad interpretation. This study aims to analyze the regulation of the principle of good faith within the law of obligations and to examine the problems arising from its application in the performance of agreements. This research employs a normative legal research method using both a statutory approach and a conceptual approach. The findings indicate that the principle of good faith plays an important role as a corrective mechanism in contractual relationships to maintain the balance of rights and obligations between the parties. Nevertheless, the lack of clear parameters regarding the application of the principle of good faith may lead to differing interpretations in judicial practice, which in turn affects legal certainty.